De-indexed estimated glomerular filtration rates for the dosing of oral antidiabetic drugs in patients with chronic kidney disease - Pluquet, Maxime; Metzger, Marie; Jacquelinet, Christian; Combe, Christian; Fouque, Denis; Laville, Maurice; Frimat, Luc; Massy, Ziad A.; Liabeuf, Sophie; Laville, Solène M. (Frontiers in Pharmacology, 2024)
Introduction Adjusting drug dose levels based on equations that standardize the estimated glomerular filtration rate (eGFR) to a body surface area (BSA) of 1.73 m² can pose challenges, especially for patients with extremely high or low body mass index (BMI). The objective of the present study of patients with CKD and diabetes was to assess the impact of deindexing creatinine-based equations on estimates of kidney function and on the frequency of inappropriate prescriptions of oral antidiabetic drugs(OADs). Methods The prospective CKD-REIN cohort is comprised of patients with eGFR <60 mL/min/1.73 m2. We compared data for three BMI subgroups (group 1 <30 kg/m²; group 2 30-34.9 kg/m²; group 3 >35 kg/m²). Inappropriate prescriptions (contraindicated or over-dosed drugs) were assessed with regard to the summary of product characteristics and the patient’s kidney function estimated with the 2009 Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, the 2021 CKD-EPI equation, the Modification of Diet in Renal Disease (MDRD), the European Kidney Function Consortium(EKFC) equation, their deindexed estimates, and the Cockcroft-Gault (CG) formula. The impact of deindexing the equations was evaluated by assessing (i) the difference between the indexed and deindexed eGFRs, and (ii) the difference in the proportion of patients with at least one inappropriate OAD prescription between the indexed and deindexed estimates. Results At baseline, 694 patients were receiving OADs. The median BMI was 30.7 kg/m², the mean BSA was 1.98 m², and 90% of patients had a BSA >1.73 m². Deindexing the kidney function estimates led to higher eGFRs, especially in BMI group 3. The proportion of patients with at least one inappropriate prescription differed greatly when comparing indexed and deindexed estimates. The magnitude of the difference increased with the BMI: when comparing BMI group 1 with BMI group 3, the difference was respectively -4% and -10% between deindexed 2021 CKD-EPI and indexed CKD-EPI. Metformin and sitagliptin were the most frequent inappropriately prescribed OADs. Conclusions We highlight significant differences between the BSA-indexed and deindexed versions of equations used to estimate kidney function, emphasizing the importance of using deindexed estimates to adjust drug dose levels – especially in patients with an extreme BMI.